Is Strategic Leadership having a mediating role in Ethiopia’s SMEs sector when it comes to Entrepreneurial Skill and Motivation? A Multivariate Investigation - Negeri, Dereje Dinsa; Wakjira, Gada Gizachew; Kant, Shashi (iRASD Journal of Management, 2023)
The major prospects for MSE will result from their participation in the global marketplace as the financial system keeps moving towards greater integration. It is widely acknowledged that SMEs are increasingly significant in producing jobs, money, and innovation. Nevertheless, there are significant issues with the caliber of management, strategic leadership, entrepreneurial skill, and motivation in this industry, shortcomings in innovation, a lack of business savvy, marketing, entrepreneurial flair, and issues with practical knowledge and HR administration. This study will analyze the impact of entrepreneurial talent and motivation on business success, with strategic leadership as a mediating factor: The situation of a few SME sectors in Ethiopia. The study employed a Quantitative research design method using surveys and questionnaires to collect data. The selections of respondents for this study will be random sampling and purposive sampling for SME owners and leaders of both zonal and town job opportunity creation and skill offices and are purposely selected to respond to the questionnaires. Since the Zone is so prominent, the researcher will select 5 towns Nagele, Adola, Shakiso, Bore, and Haro Wachu. A total of 382 respondents was selected as the sample size. The sample size will be set using Yamane (1967) due to its ease of use, taking into account the estimated total population of 2,322 owners, employment opportunity creators, and competence office executives in 5 towns. The traditional linear regression model was used for the data analysis. In this instance, data analysis included using chi square, correlation, and ordinal logistic regression to examine the impact of entrepreneurial talent and motivation on business success, with strategic leadership as a mediating factor. The findings showed that every element had a favorable and noteworthy effect on company performance.